Refractive surprise after routine cataract surgery with multifocal IOLs attributable to corneal epithelial basement membrane dystrophy. Issue 5 (May 2019) - Ho, Vivian W.M.; Stanojcic, Nick; O'Brart, Naomi A.L.; O'Brart, David P.S.
Abstract : N/A: We describe two patients in whom postsurgical refractive error occurred after routine refractive lens exchange cataract surgery with multifocal intraocular lens insertion most likely attributable to the presence of underlying corneal epithelial basement membrane dystrophy (EBMD). In Case 1, there was an unexpected hyperopic postoperative spherical equivalent refractive error of +1.50 diopters and in Case 2, a cylindrical refractive error of 2.75 diopter cylinder. We examine the possible causes of error and discuss potential management strategies to prevent and address these unpredictable postoperative outcomes. The importance of comprehensive and careful ocular surface assessment before cataract or refractive surgery as part of the presurgical workup is reemphasized. EBMD can be subtle and if overlooked, can affect the validity of biometric keratometric measurements preoperatively, resulting in an inaccurate biometry measurement, incorrect IOL selection, and reduced visual performance and patient satisfaction.